Attachment in retailing sector: retailer own-brands or manufacturer brands? - Loureiro, S. M. C. (Conference book proceedings of 9th Euromed conference of the Euromed academy of business research- innovation, entrepreneurship and Digital Ecosystems, 2016)
Highly Commended Paper award The aims of this study are (i) to explore the effect of brand credibility, familiarity and brand image on brand attachment and brand attitude; and (ii) to test how a grocery product category and the perception of quality of own-label brands versus manufacturer brands moderate the interrelationship of brand credibility, brand familiarity and brand image on brand attachment and brand attitude.